Mineral composition, phytochemical analysis, anti-oxidant and anti-diabetic activities of a polyherbal formulation- an in vitro approach - Jacob, Bindu; RT, Narendhirakannan; Nadar, MSA Muthukumar; Itsaranuwat, Pariyaporn (Chemical Data Collections, 2022)
Diabetes is a metabolic disorder with numerous complications. Combining herbal therapy appears to help treat type 2 diabetes and its complications. The focus of this research was to develop a polyherbal anti-diabetic formulation with an ethanolic extract of Gymnema sylvestre, Murraya koenigii, Cinnamomum verum, Phyllanthus emblica, and Syzygium cumini and to assess its phytochemical constituents, antioxidant activity (DPPH, ·OH, O2·, and reducing power). In vitro anti-diabetic activity of polyherbal extracts was also investigated. The mineral content of the formulation was estimated using ICP-MS. The polyherbal formulation contained a high concentration of polyphenols and flavonoids. It also had good antioxidant properties and significant -glucosidase and -amylase activities when compared to the standard drug acarbose. However, more research using an in vivo model is needed to determine the effect of free radicals and anti-diabetic activity in the treatment of type 2 diabetes. [Display omitted] .